Selection of the Method of Laser Vision Correction for the Treatment of Acquired Ametropia Following Ophthalmic Surgical Procedures - Zhmuryk, Kostiantyn (The Ukrainian Scientific Medical Youth Journal, 2026)
acquired ametropia developing after cataract, refractive, and vitreoretinal surgery remains a significant cause of visual function impairment and requires selection of an optimal enhancement strategy based on previous surgical history, corneal biomechanical status, and the patient’s functional demands. A prospective cohort analysis was conducted to evaluate the efficacy, safety, and predictability of three laser enhancement techniques for acquired ametropia in 126 patients after cataract, refractive, and vitreoretinal surgery, with assessment of clinical, topographic, and functional parameters over a 12-month follow-up period. Patients were divided into three clinical groups according to the type of primary intervention, with further subdivision based on the applied laser correction technique, which enabled a differentiated comparative analysis of surface ablation, femtosecond-assisted flap-based technology, and lenticular extraction. The comprehensive evaluation included uncorrected and corrected distance visual acuity, spherical equivalent, contrast sensitivity under photopic and mesopic conditions, tear film stability indices, Ocular Surface Disease Index, as well as corneal topo-tomographic parameters with elevation analysis and ectasia risk assessment. In patients after cataract surgery, the flap-based technique demonstrated the highest refractive predictability, statistically significantly better uncorrected distance visual acuity, and a low residual spherical equivalent while maintaining safe topographic parameters and stable mesopic contrast sensitivity, which is particularly relevant for eyes with implanted intraocular lenses. In the cohort after previous refractive surgery, surface ablation provided the most favorable biomechanical profile, minimal impact on the posterior corneal surface, and the best tear film stability parameters while preserving high functional visual quality, supporting the rationale for a flapless retreatment approach. In patients after vitreoretinal procedures, lenticular technology demonstrated the lowest residual spherical equivalent, the highest contrast sensitivity under mesopic and glare conditions, and the shortest period to normalization of ocular surface symptoms in the absence of clinically significant topographic instability, indicating functional advantages in this cohort. Statistical analysis confirmed the significance of intergroup differences across key parameters at a level of p less than 0.05. The findings demonstrate that the effectiveness of laser enhancement is determined not only by achievement of target refraction but also by comprehensive assessment of optical quality of vision, ocular surface status, and topographic safety. The results substantiate the necessity of an individualized approach to technology selection based on the type of primary intervention and corneal morphofunctional characteristics, thereby improving refractive predictability, minimizing biomechanical risks, and optimizing postoperative recovery of visual function.